Artistic Interpretation of Guests and Hospitality in Uzbek Literature - Urayeva Darmon Saidakhmedovna (International Journal on Integrated Education, 2022)
This article reveals the poetic depiction of Uzbek hospitality in written works. The image of the guest and hospitality is used to enhance the national spirit of the works, to strengthen their reality and artistic impact